Child Development through the Traditional Game of Congklak - Iyan; Muhammad Irfan (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Although traditional games have received considerable scholarly attention as learning media and instruments for child development, research specifically synthesizing the contribution of congklak to children’s cognitive, social, emotional, and motor development remains limited. This study aimed to explore the role of congklak in supporting the holistic development of primary school–aged children. A qualitative literature review was conducted using relevant scientific articles, books, and academic documents. Data were collected through documentation and analyzed using content analysis to identify recurring themes concerning the developmental benefits of congklak. The findings indicate that playing congklak supports numeracy, strategic thinking, concentration, social interaction, cooperation, sportsmanship, and fine motor coordination. The game also contributes to the preservation of local cultural values and the cultivation of positive character traits. These findings extend the literature on culture-based education by demonstrating the potential of traditional games as meaningful educational media. The study concludes that integrating congklak into learning and child development activities can support children’s holistic growth while preserving local wisdom. The findings have practical implications for teachers, parents, and educational institutions seeking to incorporate enjoyable, culturally relevant learning activities and provide a foundation for further empirical research across diverse educational contexts.